Analysis of the Effect of Oil and Energy Production on Health and Education Expenditures in Kazakhstan with Autoregressive Distributed Lag Method - Taibek , Zhazira; Kozhamkulova , Indira; Kuralbayev , Almas; Spanova , Bagdat K.; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2023)
This study analyzes the impact of Kazakhstan's oil and energy production between 2000 and 2020 on government expenditures on health and education. Kazakhstan’s total crude oil and natural gas production, gas fuel production and distribution, domestic general government health expenditures (% of GDP), out-of-pocket health expenditures (% of total health expenditures), and government expenditures on education (% of GDP) are included. ARDL analysis showed that oil and natural gas production has an impact on government expenditures on health and education. Moreover, the boundary value proved that this effect exists in both the short and long terms. ARDL analysis also showed that oil and natural gas production has a short-term effect on out-of-pocket health expenditures, but not in the long term. These findings can be interpreted as there are scientific grounds to expect that the impact of energy production on government investments in education and health will continue in the future.